Diet induced obesity modifies vitamin D metabolism and adipose tissue storage in mice. Issue 185 (January 2019) - Bonnet, Lauriane; Hachemi, Mohammed Amine; Karkeni, Esma; Couturier, Charlene; Astier, Julien; Defoort, Catherine; Svilar, Ljubica; Martin, Jean-Charles; Tourniaire, Franck; Landrier, Jean-François
Graphical abstract: Highlights: Diet induced obesity modifies the transcription of vitamin D metabolism enzymes in mice adipose tissue. Such modifications are associated to a decrease of free 25(OH)D in plasma and an increase of 25(OH)D in adipose tissue. Impact of diet-induced obesity on adipose tissue biology could contribute to the obesity-related reduction of free 25(OH)D. Abstract: Low circulating levels of total and free 25-hydroxyvitamin D (25(OH)D) indicative of vitamin D status have been associated with obesity in humans. Moreover, obesity is thought to play a causal role in the reduction of 25(OH)D levels, and several theories have been put forward to explain this relationship. Here we tested the hypothesis that obesity disrupts vitamin D homeostasis in key organs of vitamin D metabolism. Male C57BL6 mice were fed for 7 or 11 weeks on either a control diet (control, 10% energy from fat) or a high-fat diet (HF, 60% energy from fat) formulated to provide equivalent vitamin D3 intake in both groups. After 7 weeks, there was a transient increase of total 25(OH)D together with a significant decrease of plasma vitamin D3 that could be related to the induction of hepatic genes involved in 25-hydroxylation. After 11 weeks, there was no change in total 25(OH)D but a significant decrease of free 25(OH)D and plasma vitamin D3 levels. We also quantified an increase of 25(OH)D in adipose tissue that was inversely correlated to the free 25(OH)D. Interestingly, this accumulation of 25(OH)D in adipose tissue was highly correlated to the induction of Cyp2r1, which could actively participate in vitamin D3 trapping and subsequent conversion to 25(OH)D in adipose tissue. Taken together, our data strongly suggest that the enzymes involved in vitamin D metabolism, notably in adipose tissue, are transcriptionally modified under high-fat diet, thus contributing to the obesity-related reduction of free 25(OH)D.